Analisis Pengaruh Faktor Psikologis dan Religiusitas Perilaku Muslimah Kota Medan terhadap Konsumsi Kosmetik Halal dan Baik - Ira Yanti (Universitas Islam Negeri Sumatera Utara, 2018)
This research examines the behavior factor of Muslim women consumers in Medan. This study uses the moderation regression method. The study was conducted in the city of Medan with 100 Muslim women and carried out in several modern markets. The results of the study show that simultaneously the independent variables of motivation, perception, and attitudes and religiosity as moderating variables and their interactions significantly influence the consumption behavior variable. For partial tests the variables of motivation, perception, attitude, religiosity and motivational-religiosity interactions positively influence Muslim consumption behavior. For the coefficient of determination 0.21 means that about 21% of psychological factors can explain the behavior of consumers in the city of Medan. Perception is a variable that significantly influences the consumption behavior of Muslim women. The need for information and education regarding the halal and benefits of a product especially cosmetics so that Muslim women can determine products that are halal and suitable for consumption. This is to provide broader insights and knowledge for variables that influence consumption behavior.